IMPORTANCE OF INFORMATION TECHNOLOGY ON VOCATIONAL INTEREST AND VOCATIONAL ASPIRATIONS OF STUDENTS STUDYING AT HIGHER SECONDARY LEVEL - Lipika Raj; Saxena, Deepshikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education and business are the two wheels of life. Vocational education should make a person so capable through education that he can fulfill his physical needs and can maintain his life himself. Vocational education is that education through which mastery is achieved in a particular subject or field. This is skill training education, which makes students skilled in areas like computer, banking, finance, business etc. To professionalize secondary education, the Education Commission has considered in detail both the levels of education, lower secondary level and higher secondary level. According to the idea at the secondary level, 20 percent of the students from class 8 to 10 should receive vocational education. Similarly, there should be a provision of vocational education for 50 percent of the students at the higher secondary level. Education is a lifelong process. Vocational education through ITC helps in the complete education of the students.